PERDAMAIAN MENJADI PILIHAN UTAMA DALAM PENYELESAIAN KASUS KECELAKAAN LALU LINTAS - Barhamudin, Barhamudin; Dahwir, Ali (Solusi, 2021)
The purpose of this research is to see the reasons for peace being the main choice in solving traffic accident cases. This research is a normative legal research, which uses secondary data as the main data obtained from literature studies, namely by studying knowledge of the law and various regulations related to the settlement of traffic regulations. The results of the study show that peace is the solution to solving traffic accident cases because of the awareness of both parties to establish a good relationship between the families of the perpetrators or victims of accidents and the influence of customary law that still exists in society and the legal culture that exists in society. Settlement of traffic accident cases carried out amicably is a peaceful agreement made only according to customary law and causes the case to be invisible or no longer exists or so that the perpetrator of the traffic accident gets legal relief from the court; Discretion on the part of law enforcement. A peace agreement made based on customary law, but from a statutory point of view it is not binding.